Menelusuri Jejak Sejarah Kebudayaan Jambi Di Jambi Seberang - Puti Cahyo Andini; Zahara Zahara; Junita Yosephine Sinurat (Prabayaksa: Journal of History Education, 2024)
Culture is defined as thoughts, customs, something that has developed, something that has become a habit that is difficult to change. Jambi Seberang is an area rich in long and varied history. As part of Jambi Province, this region has been the center of civilization since ancient times. However, in the last decades, with rapid modernization and social change, there have been many aspects of culture and history in Jambi. The purpose of writing this article is to find out traces of the history of Jambi Seberang culture from prehistoric times until the arrivals of Islam. The research uses historical research methods with a contextual approach and data collection using library studies. The results of this article are that there are similarities in life patterns between prehistoric times and the people of Jambi Seberang now. Value traditional are also not abandonded but are incorporated into new patterns of life as an effort to adapt to the times and currents of globalization.